Development and Feasibility Validation of BreathQuest: A Project-Based Interactive Animation Application for Teaching the Human Respiratory System - Risya Pramana Situmorang; Khaerunnisa Bulan Ramadhani; Fajar Adinugraha (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Abstract concepts in the human respiratory system are hard for students to understand because conventional teaching lacks engagement. The gap between conceptual understanding and visual performance is large, underscoring the need for more innovative, interactive learning tools. Thus, the purpose of this study is to develop and explore the feasibility of a mobile Android interactive animation Project-Based Learning (PjBL)-embedded Android application named BreathQuest. The development process was conducted by type R&D with the Thiagarajan 4D model (Define, Design, Develop, Disseminate) in three-stage studies that are curriculum analysis, a design prototype (design using Adobe Animate 2D software), validation by experts (consisting of Subject matter and Media Specialists), and a one-to-one trial to five pupils. Aiken's V coefficient was calculated to assess validity. Results: Overall, high validity and feasibility, with Aiken's V coefficients ranging from 0.75 to 0.95 (Product design = 0.95, Alignment with Goals = 0.95, Ease of use = 0.90, Content = 0.85, and Interactivity = 0.75). The overall feasibility percentage for all articles was 88%. User feedback suggested that the app is visually appealing. However, there were many areas for improvement in file size, animation speed, and interoperability. BreathQuest includes core PjBL features, such as project guidelines and interactive diagrams, while allowing students to create digital posters and models. In summary, BreathQuest is a credible and workable educational tool that integrates interactive animations into PjBL to address some of the difficulties teachers face in biology education. Future research should assess its impact on learning and motivational constructs in more naturalistic classroom environments.